Tailoring the Anomalous Hall Effect in van der Waals Ferromagnet Fe3GeTe2 - WU Kaile; WANG Junshan; JIANG Jiaolin; CHAI Qian; WANG Qin; SANG Shengbo; GE Yang (Taiyuan Ligong Daxue xuebao)
[Purposes] The intrinsic magnetic moments of magnetic materials can lead to anomalous Hall effects, and the Hall resistance can be significantly reduced, thus improving the heat loss in micro- and nanoelectronic devices. Two-dimensional van der Waals magnetic materials have shown fascinating natural ferromagnetic properties at the atomic level, which has great potential in the fields of low power spintronics, quantum computing, and optical communication. [Methods] Herein, the ferromagnetism and magnetic anisotropy of bulk Fe3GeTe2 (FGT) were investigated. In addition, the anomalous Hall effect of FGT nanoflakes was studied at various temperatures and thicknesses by standard Hall bar device in detail. [Findings] The results indicate that a pronounced vertical magnetic anisotropy exists below the Curie temperature (Tc=165 K) of FGT. There is an anomalous Hall resistance of 0.764 Ω at 20 K at zero magnetic field, and it decreases to 0.332 Ω at 140 K, which proves that FGT has an anomalous Hall effect regulated with temperature. The hysteresis loop gradually changes from nearly rectangular shape to flat diamond shape, indicating that the magnetization direction of FGT has changed from out-of-plane to in-plane, which further verifies that FGT has intrinsic out-of-plane magnetic anisotropy. Furthermore, the carrier concentration (2.5×1022 cm-3 at 20 K) and mobility (13.3 cm2/(V·s) at 20 K) under large magnetic field (−6 T~6 T) are calculated.